An Injectable Nanocomposite Hydrogel Improves Tumor Penetration and Cancer Treatment Efficacy. (15th July 2022) - Luo, Feng-Qin; Xu, Wei; Zhang, Jing-Yang; Liu, Rong; Huang, Yong-Cong; Xiao, Chunsheng; Du, Jin-Zhi
Abstract: Hydrogel as a local drug depot can increase drug concentration at the tumor site. However, conventional drug-loaded hydrogel is typically formed by direct dissolution of drug molecules inside the hydrogel, which usually suffers from limited drug retention and poor tumor penetration. In this study, a nanocomposite hydrogel consisting of oxaliplatin (OXA)-conjugated G5 polyamidoamine (G5-OXA) and oxidized dextran (Dex-CHO) is constructed to improve local drug delivery. The OXA-containing nanocomposite hydrogel (denoted as PDO gel) is injectable and could maintain in vivo up to more than three weeks, which increases drug retention in tumor tissues. More interestingly, G5-OXA released from the PDO gel show potent tumor penetration mainly through an active transcytosis process. In vivo antitumor studies in an orthotopic 4T1 tumor model show that PDO gel significantly inhibits primary tumor growth as well as the metastasis. In addition, the PDO gel can also activate the immunosuppressive tumor microenvironment through immunogenic cell death effect, and further improves therapeutic efficacy with the combination of PD-1 antibody. These results demonstrate that the nanocomposite hydrogel can simultaneously enhance the retention and penetration of chemotherapeutic drugs via the combination of both advantages of hydrogel and nanoparticles, which provides new insights for the design of local drug delivery systems. Statement of significance: Hydrogel represents an important class of local drug delivery depot. However, conventional drug-loaded hydrogel is usually achieved by direct dissolution of small drug molecules inside the hydrogel, which typically suffers from limited drug retention and poor tumor penetration. Herein, we developed a nanocomposite hydrogel, which could gradually degrade and release drug-conjugated small nanoparticles (∼ 6 nm) for improved tumor penetration through the combination of an active transcytosis process and a passive diffusion process. This nanocomposite hydrogel system improved tumor penetration and retention of drug in primary tumors as well as the drug deposition in lymph nodes, which significantly suppressed tumor growth and metastasis. Graphical Abstract: Image, graphical abstract